Morphologically Complex Adjectives with a Negative Prefix: Translation Problems - Ratkus, Artūras (Vertimo studijos, 2020)
The article addresses problems of understanding and translation of morphologically complex words. It is not unusual for English adjectives with a negative prefix to have unexpected meanings that cannot be predicted based on examining the adjectives’ morphological structure. One such complex example is the adjective incapable. It is argued that this adjective has a peculiar set of meanings and uses that are independent of the positive form capable and unrelated to the adjective able. The article adduces evidence of specific uses of incapable, in which it showcases the meaning of ‘unfit for, unsuitable’ – not documented in most dictionaries.
Keywords: word building; derivation; negative prefix; translation; meaning; ambiguity